1983
DOI: 10.3109/03009748309099740
|View full text |Cite
|
Sign up to set email alerts
|

Serum Ferritin and the Assessment of Iron Deficiency in Rheumatoid Arthritis

Abstract: In order to evaluate the diagnostic and pathogenetic importance of s-ferritin and p-lactoferrin in the anemia of rheumatoid arthritis (RA), 38 patients were examined. Twenty-one out of 38 randomly selected anemic patients with classical or definite RA had iron deficiency, as estimated from the iron content in stained bone marrow aspiration. S-ferritin concentrations below 60 micrograms per litre had sensitivity and a specificity for iron deficiency of 86% and 88%, respectively, which was much better than such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
1

Year Published

1988
1988
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(36 citation statements)
references
References 14 publications
1
34
0
1
Order By: Relevance
“…As an acute phase reactant, serum ferritin increases in infections [12], rheumatoid arthritis [9], liver disease [10], cancer, and other inflammatory conditions. Ferritin level also rises with aging [7] and in the presence of other concomitant medical problems such as hypertension, chronic renal failure, chronic obstructive pulmonary disease, and diabetes [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As an acute phase reactant, serum ferritin increases in infections [12], rheumatoid arthritis [9], liver disease [10], cancer, and other inflammatory conditions. Ferritin level also rises with aging [7] and in the presence of other concomitant medical problems such as hypertension, chronic renal failure, chronic obstructive pulmonary disease, and diabetes [6].…”
Section: Discussionmentioning
confidence: 99%
“…Published series of gastrointestinal endoscopy in patients with iron deficiency anemia vary in the criteria they use to diagnose the iron deficiency, but most studies use ferritin below 20-50 ng/mL [1][2][3][4][5]. However, studies using bone marrow hemosiderin as the gold standard have shown that in older patients and/or in patients with comorbidites, iron deficiency anemia is often present despite normal levels of ferritin [6][7][8][9][10]. In a study of 101 anemic veterans who underwent bone marrow examination with hemosiderin stain, the mean ferritin in irondeficient patients was 53 ng/mL, with a range of 9-518 ng/mL [6].…”
Section: Introductionmentioning
confidence: 99%
“…In the presence of inflammation, serum ferritin levels can be high despite empty iron stores. 22,23 In such cases, 100 g/L is considered an appropriate cutoff level. 14 During or shortly after intravenous iron therapy, serum ferritin levels do not correlate with body iron stores.…”
Section: Iron Deficiencymentioning
confidence: 99%
“…There is, however, a marked increase in serum ferritin, and in RA serum ferritin levels may reach 250% of initial values.3 4 The most widely accepted explanation for the low serum iron appears to be that iron deposited in the reticuloendothelial (RE) cells is not properly released to transferrin in the circulation-that is, it is poorly re-used. 5 The RE system has a central role in iron metabolism, processing haemoglobin from senescent erythrocytes.6 Under normal circumstances the RE system provides most of the iron required for erythropoiesis, and iron storage and release by the RE system are in equilibrium.…”
mentioning
confidence: 99%